Harsh‐Environment‐Resistant OH‐Vibrations‐Sensitive Mid‐Infrared Water‐Ice Photonic Sensor. Issue 8 (13th June 2017) - Martínez, Javier; Ródenas, Airán; Stake, Andreas; Traveria, Miquel; Aguiló, Magdalena; Solis, Javier; Osellame, Roberto; Tanaka, Taro; Berton, Benoit; Kimura, Shigueo; Rehfeld, Nadine; Díaz, Francesc
Abstract : State‐of‐the‐art ultrahigh‐sensitivity photonic sensing schemes rely on exposing the evanescent field of tightly confined light to the environment. Yet, this renders an inherent fragility to the device, and since adding a protective layer disables light exposure, there exists a technology gap for highly sensitive harsh‐environment‐resistant surface photonic sensors. Here, a novel type of mid‐infrared waveguide sensors is reported which exploit vibrational resonance‐driven directional coupling effects besides absorption, with optical sensing elements that can be buried (≈1–10 µm) and resist systematic exposure to industrial environments without failure. A harsh‐environment‐resistant, fiber‐coupled, surface sensor for monitoring the structural phase of water (liquid‐supercooled‐solid), as well as the type of ice microstructure (clear rime), is shown. It is demonstrated how this type of sensor can be designed to detect ice layers with nanometric (≈100 nm) to microscopic (≈30 µm or higher) thicknesses, and the first experimental tests both in optical laboratory and in icing wind tunnel inflight aircraft simulation tests are reported. Abstract : Ice and supercooled water still puzzle scientists and engineers from a wide range of fields. Here, a harsh‐environment‐resistant photonic sensor is demonstrated that probes the phase and microstructure of water through resonant light transfer across the infrared OH‐stretch vibrational mode, finding application in fields where knowledge on the phase or composition of micro‐ to nanometric water layers is needed.